Mencegah Kasus Aborsi Dan Pembuangan Bayi Melalui Video Klip Lagu “Sempurnakan Hariku” Rey Mbayang (Analisis Semiotik Ferdinand De Saussure) - Nur Hikmatus Sobah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
One of the benefits of the semiotic approach is being able to examine in more detail the communication conveyed by works of art. In the current digital era, works of art can take the form of photography, videography, and so on, where these works of art can provide meaning or representation of a communication message. One of the works of art in the form of videography is video clips. One example of a video clip is a song entitled "Perfect My Day" sung by Rey Mbayang, which used to be trending 1 on YouTube in the music category. The background of this video is Dinda Hauw's documentary film when she is going through the process leading up to childbirth, this makes the writer interested in analyzing Ferdinand De Saussure's semiotics because the writer also has personal experience in dealing with the birth process. In this research, the researcher uses Ferdinand De Saussure's semiotic analysis method and examines the signs that refer to the video clip for the song "Sempurnaka Hariku" sung by Rey Mbayang. These signs are data such as images and other visual elements, as well as other supporting data, which will be studied and interpreted in the form of words and language. The results of the research on the video clip for the song "Perfect my day" sung by Rey Mbayang has signifiers and signifieds. It can be analyzed that the overall meaning of the various signs in the semiotic analysis is an explanation that the video clip tells about the struggles of the process of giving birth to Rey Mbayang and Dinda Hauw's first child from the beginning of the process full of anxiety, resignation, and pain until after birth it changes with a feeling of emotion, relieved and happy also grateful to have been given the mandate and gift in the form of a son from Allah SWT. The sign is that in the process of struggling to give birth, there is the role of the husband and family which are very important to support the success of the process.